Analisis Usaha Tataniaga Kopra Dalam Meningkatkan Pendapatan Keluarga Di Desa Oengkapala Kecamatan Wakorumba Utara Kabupaten Buton Utara - Sari, Nyilan; basri, muhammad; kambolong, makmur (Business UHO: Jurnal Administrasi Bisnis, 2018)
This study aims to determine the system of trade in copra business in increasing family income and to find out the obstacles faced by copra craftsmen in increasing family income in the village of Oengkapala, North Wakorumba District, North Buton Regency. Data collection techniques are carried out by means of library research and field research using interview methods, documentation, and observation...Based on the results of the research, the copra marketing channel in the study area has 2 trading channels, channel I, starting from producers to collecting traders to consumers and channel II starting from producers directly to consumers. Both of these channels have the same goal of distributing copra to consumers. The trading channel used by copra processors in Oompala Village prefers to market their copies through marketing agencies from copra processors to collecting traders. The reason for copra processors selling their copies to collectors is the amount of marketing costs and lack of transportation. The analysis of the increase in copra processing income in Oompala Village in the harvest season I was less increased while the harvest season II was in the increasing category. In the five selected informants, the copra craftsmen all experienced an increase in income during the second harvest season. because the copra processing income is due to, among other things, the difference in the selling price of copra and the difference in the amount of copra production from each coconut harvest season to copra.ABSTRAKÂ Penelitian ini bertujuan Untuk mengetahui sistem tataniaga usaha kopra dalam meningkatkan pendapatan keluarga di Desa Oengkapala Kecamatan Wakorumba Utara Kabupaten Buton Utara.Â  Teknik pengumpulan data dilakukan dengan cara studi kepustakaan dan penelitian lapangan dengan menggunakan metode wawancara, dokumentasi, dan observasiBerdasarkan hasil penelitian Saluran pemasaran kopra di daerah penelitian terdapat 2 saluran tataniaga, saluran I mulai dari produsen kepedagang pengumpul hingga kepada konsumen dan saluran II mulai dari produsen langsung kepada konsumen. Kedua saluran ini memiliki tujuan yang sama yaitu mendistribusikan kopra sampai ke konsumen. Salurantataniaga yang digunakanolehpengolahkopra di Desa Oengkapala lebih memilih memasarkan kopranya melalui lembaga pemasaran dari pengolah kopra kepedagang pengumpul. Alasan pengolah kopra menjual kopranya kepada pedagang pengumpul yaitu besarnya biaya pemasaran dan kurangnya transportasi. Analisis peningkatan pendapatan pengolah kopra di Desa Oengkapala pada musim panen I kurang meningkat sedangkan musim panen II termaksud dalam kategori meningkat. Dalam kelima informan terpilih yakni pengolah kopra semuanya mengalami peningkatan pendapatan pada musim panen II dikarenakan Pendapatan pengolah kopra ini disebabkan antara lain perbedaan hargajual kopra dan perbedaan besarnya hasil produksi kopra masing-masing musim panen kelapa menjadi kopra.